1978
DOI: 10.1007/bf01642161
|View full text |Cite
|
Sign up to set email alerts
|

Diarrhea in newborn cynomolgus monkeys infected with human rotavirus

Abstract: Of six newborn cynomolgus monkeys (Macaca fascicularis) naturally delivered and normally nursed five developed diarrhea after oral administration of human rotavirus. Virus excretion was observed in the stool of four animals. This virus was transmitted to four out of six other monkeys causing diarrhea in only one animal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
9
0

Year Published

1982
1982
2009
2009

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 7 publications
2
9
0
Order By: Relevance
“…Accordingly, many studies on the pathogenesis of and immunity to such agents have been performed with nonhuman primates. Very few studies, however, have been conducted with rotavirus in any nonhuman primate species (21,23,26,31,36,41,55). A major limitation for performing such studies has been the absence of a challenge strain of simian rotavirus that will consistently result in productive infections in a nonhuman primate species after oral challenge.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, many studies on the pathogenesis of and immunity to such agents have been performed with nonhuman primates. Very few studies, however, have been conducted with rotavirus in any nonhuman primate species (21,23,26,31,36,41,55). A major limitation for performing such studies has been the absence of a challenge strain of simian rotavirus that will consistently result in productive infections in a nonhuman primate species after oral challenge.…”
Section: Discussionmentioning
confidence: 99%
“…Although several rotavirus challenge studies have been conducted with these animals, the first of which was reported in 1976 (55), very little is known about rotavirus infections in any nonhuman primate species. Several investigators have reported that oral inoculation of different nonhuman primates, including several types of monkeys as well as baboons, with either culture-adapted simian (SA11) or human (Wa) rotavirus or fecal preparations of human rotaviruses, will cause diarrheal illness in most animals during their first week of life (21,23,26,31,36,41,55). However, after that time, essentially no illness was observed, and most of the older animals neither shed virus nor seroconverted.…”
mentioning
confidence: 99%
“…Although several NHP species, including chimpanzees and baboons as well as rhesus, vervet, pigtailed, and squirrel monkeys, have been reported to seroconvert to rotavirus with high, virus-specific antibody titers, no studies on cell-mediated immune responses have been conducted with an NHP model in the context of rotavirus (11,14,29,36,43). One reason is that clinical disease associated with rotavirus infection in NHPs, which has been reported to be limited to the first days or weeks of life (20,21,29,36,42), is difficult to produce experimentally.In this study, the cell-mediated immunological responses to rotavirus infection in juvenile rhesus macaques that were housed in biosafety level 2 facilities of the Tulane National Primate Research Center (TNPRC) were evaluated. We anticipated that cell-mediated immune responses could be measured in these animals by the time passive maternally acquired immunity subsided, i.e., at between 4 and 6 months of age.…”
mentioning
confidence: 99%
“…Although several NHP species, including chimpanzees and baboons as well as rhesus, vervet, pigtailed, and squirrel monkeys, have been reported to seroconvert to rotavirus with high, virus-specific antibody titers, no studies on cell-mediated immune responses have been conducted with an NHP model in the context of rotavirus (11,14,29,36,43). One reason is that clinical disease associated with rotavirus infection in NHPs, which has been reported to be limited to the first days or weeks of life (20,21,29,36,42), is difficult to produce experimentally.…”
mentioning
confidence: 99%
“…Experimental rotaviral infection with diarrhea was reported to occur in newborn rhesus monkeys reared by formula-feeding for 24 hr after delivery (13). Other similar studies used baboons and cynomolgus monkeys nursed by their mothers for the entire duration of the experiments (3,6). In these studies of monkeys, the simian SAll virus or a wild-type rotavirus was used.…”
mentioning
confidence: 99%